Combinations of approach and avoidance crafting matter: Linking job crafting profiles with proactive personality, autonomy, work engagement, and performance - Zhang, F.; Tims, M.; Parker, Sharon (2024)
Traditional variable-centered job crafting research typically examines individual job crafting behaviors in isolation. This study builds upon existing person-centered job crafting research, aiming to further validate job crafting profiles based on the job demands-resources model. By testing profile similarity across different samples and time points, we identify three consistent job crafting profiles: proactive crafters, characterized by a high use of approach crafting and a moderate use of avoidance crafting; active crafters, who exhibit an average level of all job crafting strategies; and reactive crafters, marked by a low use of approach crafting strategies but a relatively high use of avoidance crafting. As theorized, the proactive crafters profile emerged as the most desirable, displaying the highest levels of self-reported work engagement, task performance, and organizational citizenship behavior. This finding underscores that avoidance crafting becomes less detrimental when used alongside approach crafting. Moreover, our study reveals that proactive personality and job autonomy significantly increase the likelihood of employees being proactive crafters, offering empirical support for the notion that avoidance crafting can be an integral part of a proactive goal when combined with approach crafting.